Metal-organic frameworks: towards greener synthesis - Howie, Rowena Anne (2017)
Metal Organic Frameworks (MOFs) are an interesting class of porous materials, for potential commercial applications such as storage and separation of gases. However, the industrial use of MOFs would require their synthesis on a much larger scale, necessitating the development of scalable synthesis techniques that are both greener and faster than those currently employed. This Thesis describes the recent progress towards the clean and scalable synthesis of MOF materials via the use of high temperature water (HTW) and related solvents. Supercritical ethanol extraction is also presented as a greener alternative for the removal of impurities, such as unreacted ligand, from within the pores of MOFs. Chapter 1 introduces the concepts explored during this work, such as green chemistry, and includes a brief overview of MOF materials, covering their properties, applications and synthesis, as well as the challenges facing their industrial implementation. The properties of HTW and supercritical ethanol, in relation to their use as cleaner solvents for MOF processing, are summarised and the aims of this project stated. The high pressure equipment and analysis techniques used during this work are then described in Chapter 2. Detailed descriptions and standard operating procedures for the following equipment are included: high pressure mini autoclaves; a continuous flow HTW reactor for the synthesis of MOF materials; and a supercritical ethanol extraction set up, for the removal of impurities from within MOF samples. (Information regarding a new continuous flow rig developed during this project can be found in Chapter 6). The use of supercritical ethanol as a cleaner alternative method for the removal of uncoordinated ligand from within the pores of MOF materials is explored in Chapter 3, where MIL 53(Al), an archetypal aluminium MOF, was used as an example throughout. The impact of this technique on the properties of the resulting MOF samples are also considered within this chapter. Chapter 4 illustrates the broad applicability of HTW to MOF materials, demonstrating the synthesis of a wide range of MOFs, primarily as fast batch reactions. Unlike typical MOF syntheses which require several days, reaction times of just 10 minutes were used during this investigation. This highlights the fact that the synthesis of MOFs in HTW is both faster and cleaner than many previous methods. The variety of MOFs synthesised in this chapter contain different metal centres and ligands, confirming that HTW synthesis is not limited to a small sub set of MOF materials. MOFs successfully synthesised in this manner include: MIL 96(Al); NOTT 300(Al); NOTT-300(In); scandium terephthalate, plus amine and nitro group containing analogues; and MOF 74(Ni). The synthesis of a larger (10 g) sample of one of these MOFs, NOTT 300(Al), is the subject of Chapter 5, which can be viewed as a case study into the challenges facing the scalable synthesis of MOF materials in both batch and continuous flow. Building on experience gained during this investigation, a new continuous flow HTW MOF synthesis reactor was designed and constructed, the development and testing of which forms the basis of Chapter 6. This new reactor was then implemented in Chapter 7, which describes the HTW synthesis of a range of functionalised aluminium MOFs, based on the MIL 53(Al) structure, containing additional amine or nitro groups, in both batch and flow. These MOFs were the first examples of the synthesis of functionalised MOF materials in HTW, demonstrating the flexibility of this technique and suggesting that it may be successfully applied to a much wider range of MOFs in the future. Finally, Chapter 8 revisits the aims set out in Chapter 1, providing a summary of the progress made towards meeting each aim and highlighting possible future directions.